1988
DOI: 10.1002/hep.1840080619
|View full text |Cite
|
Sign up to set email alerts
|

The development of the intrahepatic bile ducts in man: A keratin-immunohistochemical study

Abstract: The development of the intrahepatic bile ducts in man was studied using an immunohistochemical technique on 56 liver specimens ranging in age from 6 weeks of gestation to 8 months after birth. On paraffin sections, two monoclonal anticytokeratin antibodies (CAM 5.2 and KL-1) that normally stain both hepatocytes and bile duct cells and two polyclonal anticytokeratin antisera that in normal adult liver stain bile ducts only were applied. For immunohistochemical staining of cryostat sections (only available from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
254
2
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(280 citation statements)
references
References 29 publications
20
254
2
4
Order By: Relevance
“…We also observed ductular keratins 8 and 18) to express ductular cytokeratins (cytokeratins 8 and 18 / 17 and 19) as they develop to become bile ductular cells. [13][14][15][16][17] To determine if the cells of the limiting ary atresia cases. The control ductules failed to show PCNA plate are capable of actual proliferation during fetal liver staining in their nuclei, but, in biliary atresia, a low level of development, we double-stained our specimens with PCNA PCNA staining was consistently observed.…”
Section: Control Infant Livers and Extrahepatic Biliary Atresia Wementioning
confidence: 99%
See 1 more Smart Citation
“…We also observed ductular keratins 8 and 18) to express ductular cytokeratins (cytokeratins 8 and 18 / 17 and 19) as they develop to become bile ductular cells. [13][14][15][16][17] To determine if the cells of the limiting ary atresia cases. The control ductules failed to show PCNA plate are capable of actual proliferation during fetal liver staining in their nuclei, but, in biliary atresia, a low level of development, we double-stained our specimens with PCNA PCNA staining was consistently observed.…”
Section: Control Infant Livers and Extrahepatic Biliary Atresia Wementioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23] These studies have further supported the hepadevelopment remains a subject of controversy, although tocytogenic theory. there has been recent evidence that they form from heCytokeratins are the intermediate filaments of the cypatocytes.…”
mentioning
confidence: 97%
“…They are abortions (spontaneous and artificial), intrauterine fetal death, and autopsies. The gestational ages (weeks) of the 32 fetal livers were as follows: 17,18,19,21,23,24,26,29,30,36,38, and 40. The sex was unclear.…”
Section: Methodsmentioning
confidence: 99%
“…MarieJosé Vanstapel discovered that cholangiocytes are marked by immunostaining for S-100 protein 17 and for keratins using polyclonal antikeratin antiserum. 18 Peter Van Eyken subsequently demonstrated by use of monoclonal antibodies against individual keratins that hepatocytes express keratin 8 (K8) and K18, whereas cholangiocytes express K7 and K19, 19 in addition, thus providing the basis for cell lineage studies in embryonic development of intrahepatic bile ducts 20,21 and in HCCs. 22,23 During embryonic development, K19 is not only a marker of cholangiocytes, but of primitive hepatoblasts as well, 24 and the liver cancer studies revealed that many tumors which were morphologically diagnosed as HCCs express bile duct-type K7 and/or K19, indicating a nonhepatocellular trait in HCCs.…”
Section: Histogenesis Of Liver Cancermentioning
confidence: 99%